Game-Based Microlearning Strategy to Enhance Migrant Students' Learning Engagement at SB SIKL Serdang Malaysia - Salma, Fima Nursalnia; Nurjanah, Siti; Kholis, K (Al'ulum Jurnal Pendidikan Islam, 2026)
This study aims to determine the effectiveness of microlearning strategies based on snake and ladder games in increasing the learning involvement of migrant students at Sekolah Indonesia Kuala Lumpur (SIKL) Serdang, Malaysia, especially in Islamic Religious Education. The research used a quantitative approach with a pre-experimental one-group pretest-posttest design. Data was obtained through a questionnaire that measures student learning engagement based on three aspects, namely behavioral, emotional, and cognitive, and supported by observation and documentation. Data analysis was carried out by statistical test to compare the level of learning engagement before and after the implementation of the strategy. The results show that the application of a microlearning strategy based on the snake and ladder game is able to significantly increase student learning engagement. Therefore, this strategy is recommended as an interactive learning alternative, contextual, and inclusive in non-formal education.